[BOOK REVIEW] DEVELOPING INTERACTIONAL COMPETENCE IN A JAPANESE STUDY ABROAD CONTEXT - Nurjaleka, Lisda (Universitas Negeri Semarang, 2019)
(Developing Interactional competence in A Japanese Study Abroad Context) is a book focusing on second language learning acquisition by Naoko Taguchi. It is a study describing the process of second language acquisition which focuses on the development of interactional competence in a Japanese ゛study abroad゛ context. The book contains nine chapters, which explain the introduction of the study, the method, speech style and style shift in language learning; how incomplete sentences in the Japanese language are produced; and the case histories in the study abroad experience. This book is a qualitative study of learners studying abroad in Japan and explains changes in their interactional competence, such as change in the use of speech styles, style shifting between the polite and plain forms, and the function of incomplete sentences. This function is one of the main characteristics of the Japanese language. The main goal of this book is to enable researchers such as postgraduate students to learn more about second language acquisition and to assist learners in becoming competent L2 speakers in the target community   Book review kali ini membahas buku yang berkaitan dengan Akuisisi pembelajar bahasa Kedua denga judul `Developing Interactional Competence in a Japanese Study Abroad Context` oleh Naoko taguchi. Di dalam buku ini membahas tentang proses akuisis bahasa kedua yang memfokuskan pada pembelajaran studi di luar negeri untuk membangun kompetensi interaksional bahasa Jepang. Buku ini terdiri dari Sembilan bab yang menjelaskan tentang pengantar mengenai penelitian kali ini, metode penelitian, speech style dan style shif dalam pembelajaran bahasa, bagaimana kalimat tidak lengkap terbentuk dalam bahasa Jepang dan deksriptif kualitatif mengenai studi kasus pengalaman studi di luar negeri. Buku ini termasuk kedalam penelitian kualitatif pembelajar bahasa Jepang di Jepang yang melakukan studi lanjut dan menjelaskan bagaimana perubahan dalam kompetensi interaksional mereka, seperti perubahan penggunaan dalam speech style dan style shifting antara bentuk polite dan bentuk normal. Dan bagaiman fungsi-fungsi dari kalimat-kalimat tidak utuh. Tujuan utama dari buku ini adalah memungkinkan bagi para peneliti seperti mahasiswa pasca sarjana dan peneliti pemula untuk belajar mengenai akuisisi bahasa kedua dan membantu para pembelajar menjadi kompeten sebagai Penutur bahasa kedua di komunitas target dalam hal ini di Jepang.